The Value of Pancasila as Strengthening the Character Building of the Indonesian Nation - Hanpalam, Teodorikus (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2021)
This paper aims to: (1). To find out the value of Pancasila as a strengthening of the nation's character building. (2). To instill the value of Pancasila in building national character. (3). As an illustration of the importance of safeguarding the value of Pancasila and strengthening the nation's character in educational institutions. The writing method used in this research is literature study. Benefits of Writing: (1). As a scientific study, this writing can be used as reading material and reference about the value of Pancasila as a reinforcement of the building character. (2). For the author to get an overview of how the value of Pancasila is in building the character of the nation. (3). Providing information as an illustration of the value of Pancasila and efforts to build the nation's character.